Телеграм бот помічник роботодавцям - Карась, Мар'яна Юріївна; Karas, Mariana Yuriivna (Національний університет "Львівська політехніка", 2024)
В процесі написання даної бакалаврської кваліфікаційної роботи було створено програмного робота Telegram-бота “HelperBot”, що призначений для автоматизації розміщення оголошень про необхідну до виконання роботу роботодавцями у месенджері Telegram. В процесів дослідження проведено аналітичний огляд сучасних месенджерів та Telegram-ботів. Для розробки обрано мову програмування Python та інтегроване середовище PyCharm, а також використано необхідні бібліотеки для реалізації асинхронної взаємодії з користувачем. Робота охоплює етапи проєктування алгоритмів, створення інтерфейсу, логіки опрацювання запитів та перевірки введення даних. В результаті було створено Telegram-бота з можливістю створення оголошень, їх публікації, попереднього перегляду та закриття оголошень про роботу. У процесі симуляції взаємодії Telegram-бота з користувачем було підтверджено його працездатність, зручність у використанні та практичну ефективність.

This bachelor’s thesis is dedicated to the development of a robotic system for abrasive blasting (sandblasting) of surfaces, designed to remove contaminants such as rust, paint, and deposits from various types of structures. The primary objective of this study is to improve the quality and safety of surface cleaning through process automation, which reduces the operator’s exposure to hazardous conditions while ensuring consistently high processing standards. The work explores the fundamentals of abrasive cleaning methods, analyzes existing automated systems, and, based on this analysis, proposes a custom-designed solution. I have developed the structure of a robot equipped with a manipulator mounted on a mobile platform, designed the control system, modeled the computer vision functionality, analyzed system movements, and evaluated overall performance. Particular attention was given to the design of the computer vision subsystem, which enables real-time identification of surface types, conditions, and the degree of cleanliness. The proposed solution shows strong potential for implementation in industrial facilities and large-scale construction projects, aiming to increase both productivity and operational safety. Total length of the thesis: 84 pages, 14 figures, 27 references.
Telegram bot for employer’s assistance
Keywords: 6.152.00.00; Telegram-бот; Python; програмний бот; алгоритм; месенджер